Analyzing Context Clues in Novel Based on Bauman's Theoretical Framework - Laily, Almadani Durotul (Journal of Linguistics and Social Sciences, 2023)
Context clues are valuable tools employed by authors to assist readers in comprehending unfamiliar or complex vocabulary. These clues, whether intentionally or inadvertently provided, facilitate the reader's understanding and interpretation of the word in question. Drawing upon Bauman's theoretical framework, the present study sought to investigate the diverse contextual cues utilized by the author within the literary work entitled "Jet Black and the Ninja Wind." The primary objective of this investigation was to gain a comprehensive understanding of the semantic nuances associated with unfamiliar lexical items employed in the literary work "Jet Black and the Ninja Wind." Additionally, this study aimed to identify and analyze the predominant types of contextual cues prominently present within the book above. In this study, a descriptive qualitative approach was utilized by the researcher. The data collection method employed in this study involved the utilization of documentation as a means to gather relevant information. The human instrument, the researcher herself, was utilized as the primary instrument in this research endeavor. The data analysis process in this study consisted of three distinct stages: data condensing, data displaying, and conclusion drawing. Investigator triangulation was also employed in this study to corroborate and substantiate the findings derived from the comprehensive analysis of the collected data. After conducting an extensive examination of Jet Black and the Ninja Wind, 56 unfamiliar terms were identified. These terms were subsequently categorized into four distinct groups, taking into consideration contextual clues that suggested each group possessed a particular semantic significance. The categorization of context hint types encompasses inference/general cues, synonym/restatement clues, antonym/contrast clues, and definition/explanation clues. In the literary work entitled "Jet Black and the Ninja Wind," the author predominantly utilized various types of context clues, including but not limited to synonym/restatement clues, inference/general hint clues, definition/explanation clues, and antonym/contrast clues.